2011
DOI: 10.1177/1933719111404611
|View full text |Cite
|
Sign up to set email alerts
|

Differential Methylation of Imprinted Genes in Growth-Restricted Placentas

Abstract: A complex network of epigenetic factors participates in regulating the monoallelic expression of a small subset of genes (~1%) in the human genome. This phenomenon goes under the definition of genomic imprinting, a parent-of-origin effect that, when altered during early embryogenesis, may influence fetal development into adulthood. Pertubations in genomic imprinting have been associated with placental and fetal growth restrictions. We analyzed the differential DNA methylation of all known imprinted genes on 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Rapid advancements in the discovery of integrated regulation of neuropeptide homeostasis within the brain and placenta [63, 64] have led to the concept that the placenta may be like a “third brain” linking the developed (maternal) and developing (fetal) brains [64, 65]. Maternal perturbations are conveyed to the fetus via the placenta, in the expression of transporters that regulate the flux of glucose, amino acids, and vitamins required for growth and development [66].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid advancements in the discovery of integrated regulation of neuropeptide homeostasis within the brain and placenta [63, 64] have led to the concept that the placenta may be like a “third brain” linking the developed (maternal) and developing (fetal) brains [64, 65]. Maternal perturbations are conveyed to the fetus via the placenta, in the expression of transporters that regulate the flux of glucose, amino acids, and vitamins required for growth and development [66].…”
Section: Methodsmentioning
confidence: 99%
“…Maternal perturbations are conveyed to the fetus via the placenta, in the expression of transporters that regulate the flux of glucose, amino acids, and vitamins required for growth and development [66]. Thus, the placenta serves as the “master regulator” in utero and plays a highly functional role in shaping fetal development [65]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Chu et al (15) found large regions of hypomethylation in placenta compared with maternal blood cells; however, the analysis was limited to chromosomes 13,18, and 21. Further study of DNA methylation in placenta is warranted because changes in placental methylation have been associated with infant growth rate, pre-eclampsia, and preterm delivery (17)(18)(19)(20)(21). Furthermore, the placenta is the key mediator of environmental exposures affecting developmental programming of the fetus, which can have long-lasting effects on health (22).…”
mentioning
confidence: 99%
“…Genomic imprinting is an epigenetically driven phenomenon that results in the preferential silencing of a copy of an autosomal gene while the other copy is expressed (Hutter et al 2010). Imprinted genes that are exclusively expressed in the placenta play a role in the distribution of maternal resources to the fetus (Lambertini et al 2011). According to the genetic conflict theory of imprinting, maternally imprinted genes that are paternally expressed, such as Igf2, Peg1/Mest and Peg3, promote fetal growth, while paternally imprinted genes that are maternally expressed, such as H19, Igf2r, Cdkn1c, Phlda2 and Grb10, act as growth suppressors (Miguel Constância et al 2002, Constancia et al 2005, Tunster et al 2011, Janssen et al 2016 (Fig.…”
Section: Imprinted Genes and Epigenetic Changes Are Involved In The Cmentioning
confidence: 99%